Produksi Enzim Lakase Oleh Jamur Trichoderma Asperellum Lbkurcci Dengan Variasi Penambahan CuSO4 Menggunakan Bioreaktor Tray Secara Solid State Fermentation (SSF) - Nurliati, Ivanna; Helianty, Sri; Dahliaty, Andi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Laccase is one of the ligninolityc enzymes that capable to degrade lignin. This ability can be used for the pretreatment of lignocellulosic materials in the bioethanol production and lignin degradation in pulp. There are diverse sources of laccase producing like fungi, plants and bacteria. This research is, conducted to the production of laccase enzyme using Trichoderma asperellum LBKURCC1 with bioreactor tray using solid state fermentation (SSF) method with rice straw substrate. The research was purposed to determine the effect of CuSO4 inducer and know the best fermentation time on production of enzyme by Trichoderma asperellum LBKURCC1. Fermentation was carried out with time variations that are 5-10 days and variations of CuSO4 that are 0,25-0,75 g/L with substrate size Â±0,5 cm, the bed depth on the tray 3 cm. Fermentation using room temperature and pH is 5,5. The result showed that the highest laccase enzyme activity was obtained on CuSO4 inducer 0,50 g/L and 7 days fermentation with average laccase enzyme activity was 19,270 U/L.Keywords: Inducer, Laccase, Rice straw, Solid state fermentation, Trichoderma asperellum.